A brief insight to Pakistan’s Pharmaceutical industry- A critical review study - Aqsa Jannat, Nusrat Shafiq, Maha Hanif, Maryam Riasat, Sadia Rafique (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: This is a review article, which focused upon Pakistan’s pharmaceutical industry. This industry has fallen into the trap of our country’s buckwheat. Basically, it’s the main concern of pharmaceutical industries of Pakistan, one of the present standing position or top most sold products. Method: This is a comparison between industry from start to form or global level. It has been a detailed review of Pakistan’s import and export products over the years. This article gives an overview on APIs, how they are synthesized and major exporters of APIs. Drugs formulations are also discussed in it. Formulation of drugs are solid, liquid and semi solid. Moreover, it also focused at the limitations and strengths of the factors that are important in determining the strength. Results: The pharmaceutical business has a strong capacity for innovation, and governments should conduct studies and encourage discussion on how to improve this capacity without endangering public health. Practical implication: The strength of each pharmaceutical industry based upon quality goods, providing values, services excellence.There are concerns about the current rules in Pakistan for evaluating the quality of pharmaceuticals raw materials (APIs).The pharmaceutical industry strengths could include low operating overhead, firm fiscal management, low staff turnover, high return on investment (ROI), state-of-the-art laboratory equipment and an experienced research staff. Conclusion: The medical system in a country is crucially dependent on the pharmaceutical sector. This study’s goal was to shed light on Pakistan’s entire pharmaceutical sector, including startups, imports, exports, and detail of APIs. The pharmaceutical industry in Pakistan is still in its early stages, but it has managed to establish a small presence in Asia-Pacific market. Keywords: Brands, Ointment, ROI, spurious drugs and PIDB